2021
DOI: 10.1186/s12943-021-01373-z
|View full text |Cite
|
Sign up to set email alerts
|

Histone citrullination: a new target for tumors

Abstract: As the main protein components of chromatin, histones play central roles in gene regulation as spools of winding DNA. Histones are subject to various modifications, including phosphorylation, acetylation, glycosylation, methylation, ubiquitination and citrullination, which affect gene transcription. Histone citrullination, a posttranscriptional modification catalyzed by peptidyl arginine deiminase (PAD) enzymes, is involved in human carcinogenesis. In this study, we highlighted the functions of histone citrull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 166 publications
1
67
0
Order By: Relevance
“…Studies in cancer cell lines demonstrated that the occurrence of histone citrullination, mediated by PAD4, on p53-regulated genes, including p21, CIP1, WAF1 and OKL38 repressed their transcriptional activation, leading to cell cycle arrest and apoptosis [ 158 , 159 ]. These findings are in support of the notion that targeting PAD4 and other PAD enzymes may provide a novel strategy to inhibit tumor growth [ 160 ]. Immunohistochemistry and western blot detection demonstrated PAD4 overexpression in various tumor types, especially adenocarcinoma.…”
Section: Protein Citrullination As a Hallmark Of Immune Disorderssupporting
confidence: 84%
“…Studies in cancer cell lines demonstrated that the occurrence of histone citrullination, mediated by PAD4, on p53-regulated genes, including p21, CIP1, WAF1 and OKL38 repressed their transcriptional activation, leading to cell cycle arrest and apoptosis [ 158 , 159 ]. These findings are in support of the notion that targeting PAD4 and other PAD enzymes may provide a novel strategy to inhibit tumor growth [ 160 ]. Immunohistochemistry and western blot detection demonstrated PAD4 overexpression in various tumor types, especially adenocarcinoma.…”
Section: Protein Citrullination As a Hallmark Of Immune Disorderssupporting
confidence: 84%
“…With respect to the role of citrullination in the oral mucosa, Arita et al reported that PAD contributes to the integrity of the stratum corneum of the oral mucosa by citrullinating filaggrin and profilaggrin in the rat palate [ 32 ]. In addition to filaggrin, other citrullinated peptides with physiological roles include the glial cell fibrillary acidic protein [ 33 ], myelin basic protein [ 34 ], and histones [ 35 ]. For example, physiologically, citrullinated vimentin causes intermediate filament proteins to lose their ability to polymerize and form filaments [ 36 ], and citrullinated histones are involved in the regulation of gene expression and neutrophil extracellular trap formation.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to histone deimination, while only PAD4 has a classical nuclear translocation signal, both PAD2 and PAD3 are also reported with nuclear location and found to deiminate histones [ 11 , 16 , 17 , 31 , 33 ]. Histone citrullination is strongly associated to tumours [ 54 ] and CitH3 is a common marker for NETosis, which has also been used as an indicative marker for cancer-associated inflammatory processes. For example, such processes have been associated with awakening dormant cancer cells [ 55 ].…”
Section: Discussionmentioning
confidence: 99%